LaI2@(18,3)SWNT: the unprecedented structure of a LaI2 "Crystal," encapsulated within a single-walled carbon nanotube. - Friedrichs, S; Kirkland, A; Meyer, R; Sloan, J; Green, M (2005)
The novel crystallization properties of nano-materials represent a great challenge to researchers across all disciplines of materials science. Simple binary solids can be found to adopt unprecedented structures, when confined into nanometer-sized cavities, such as the inner cylindrical bore of single-walled carbon nanotubes (SWNT). Lanthanum iodide was encapsulated within SWNTs and the resulting encapsulation composite was analyzed using energy-dispersive X-ray microanalysis (EDX) and high-resolution transmission electron microscopy (HRTEM) imaging techniques, to reveal a one-dimensional crystal fragment, with the stoichiometry of LaI2, crystallizing in the structure of LaI3 with one third of the iodine positions unoccupied. A complete characterization of the encapsulation composite was achieved using an enhanced image restoration technique, which restores the object wave from a focal series of HRTEM images, providing information about the precise structural data of both filling material and host SWNT, and thereby enabling the identification of the SWNT chirality.